A Framework to The Inventory of Cuture-based Tourism Products - Henriques, Cláudia; Guerreiro, Manuela; Mendes, Júlio (E-Journal of Tourism; Volume 4 Number 1 (March 2017)DO - 10.24922/eot.v4i1.30163, 2017)
Cultural Tourism is a promising market segment with higher growth rates than other niches. World Tourism Organization (UNWTO) data indicate that the proportion of international trips accounted for cultural motivations grew from 37% in 1995 to 40% in 2004. Additionally, UNWTO (2015) considers that this type of tourism could, in the future, increase competitiveness, create employment opportunities, generate income for investment in preservation, and simultaneously contribute to a sense of pride and self-esteem among host communities. In this article the authors propose a reflection on cultural tourism, based on the questioning of concepts such as tourism and culture, experiences and transformations. To this purpose, this paper aims to come up with a framework upon which tourism destinations can develop culture-based tourism products.
Keywords: tourism, culture, cultural tourism, tourism experience